Application of the 3G PCS technologies to the mobile subsystem of the next generation tactical communications systems - Çayırcı, E. (Erdal) (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1999., 2000)
The advances in high-speed computations, multimedia and wireless communications promise new opportunities to develop more robust and agile battlefield communications systems. However, there are some major distinctions between the military and commercial communications. We can enumerate the most basic two of them as the hostile environment in battlefield, and the rapid deployment requirement. In our study, we discuss how to employ emerged and evolving civilian commercial technologies, namely the third generation (3G) Personal Communications Services (PCS) techniques for military communications in spite of the existence of such distinctions. We propose an approach called Virtual Cell Layout (VCL) in which the communications area is tessellated with regularly shaped fixed virtual cells starting from a geographic reference location. The radio resources are managed in a multitier hybrid network by employing both cellular and ad hoc techniques and using VCL.We also propose a simulation approach for the performance evaluation of the tactical communications systems. In this approach, the commands entered during the military computer aided exercises are replayed by running a constructive (combat) model which generates mobility, posture and status data for a number of units, then these data are enhanced and drive a simulation which produces the data related to the performance metrics. The evaluated performance of the system shows that the VCL based architecture satisfies the rapid deployment requirement and gives an acceptable grade of service.
Keywords: Personal communication service systems.; Wireless communication systems.; Mobile communication systems.; Communications, Military.